2022
DOI: 10.3389/fsurg.2022.936720
|View full text |Cite
|
Sign up to set email alerts
|

A Strong Correlation Between the Severity of Flatfoot and Symptoms of Knee Osteoarthritis in 95 Patients

Abstract: ObjectiveThe purpose of this study is to assess the association between the presence and severity of flatfoot and symptoms of knee OA.Methods95 participants with knee OA were recruited from a patient cohort at a regional hospital. Symptoms of knee OA, including knee degeneration, femorotibial alignment, pain, stiffness and dysfunction were assessed using the Kellgren-Lawrence (K-L) grading system, femoral-tibial angle (FTA), and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC). Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The calcaneus valgus is obvious, the foot bone hyperplasia, plantar fasciitis, etc., and the foot presents discomfort and pain, which further affects the patient’s standing, walking posture, and lower limb force line changes. 22 Nguyen A D 23 has reported studying the relationship between lower limb alignment feature selection and Q angle in the pelvis, hip, knee, and foot, and finally concluded that Q angle poses a certain risk to the entire lower limb.Min Z 12 conducted a correlation analysis between the severity of flat foot and knee osteoarthritis after grouping, and the results showed that the severity of flat foot was significantly related to the symptoms of knee osteoarthritis. They believed that patients with flat foot and their severity should be considered when treating knee osteoarthritis.The balance movement ability of patients with flat foot can change due to changes in the foot structure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcaneus valgus is obvious, the foot bone hyperplasia, plantar fasciitis, etc., and the foot presents discomfort and pain, which further affects the patient’s standing, walking posture, and lower limb force line changes. 22 Nguyen A D 23 has reported studying the relationship between lower limb alignment feature selection and Q angle in the pelvis, hip, knee, and foot, and finally concluded that Q angle poses a certain risk to the entire lower limb.Min Z 12 conducted a correlation analysis between the severity of flat foot and knee osteoarthritis after grouping, and the results showed that the severity of flat foot was significantly related to the symptoms of knee osteoarthritis. They believed that patients with flat foot and their severity should be considered when treating knee osteoarthritis.The balance movement ability of patients with flat foot can change due to changes in the foot structure.…”
Section: Discussionmentioning
confidence: 99%
“…Especially when it comes to changes in the stable shape of a certain structure in the lower limb as a whole, it will have a certain impact on the entire lower limb force line, leading to secondary diseases. [11][12][13] Our research group has found clinically that some patients who come to our hospital with flat foot as a diagnosis have patellar instability, while most patients who come to our hospital with patellar dislocation have flat foot. Based on this issue, this study explored the correlation and risk factors between adolescent flat foot and developmental patellar instability.…”
mentioning
confidence: 99%
“…There is a substantial relationship between the severity of the flattening of the foot arch and the symptoms of KOA, as measured by Clarke's angle (CA). This implies that the degree of flattening of the foot arch is directly associated to the prevalence and severity of symptoms reported by patients with KOA [12]. Daman K. Jha et al [13] found that hallux valgus deformities, pes planus (flatfoot), and hindfoot varus were the most prevalent foot deformities associated with KOA.…”
Section: Literature Reviewmentioning
confidence: 99%